Increased sprint performance with false step in collegiate athletes trained to forward step. Issue 8 (14th September 2022) - Schwenzfeier, Aaron; Rhoades, Jesse Lee; Fitzgerald, John; Whitehead, James; Short, Martin
ABSTRACT: The ability to achieve rapid acceleration is a crucial asset for athletes. An emergent tactic to achieve this advantage has been the performance of a backward step when beginning a sprinting action. This action has even gained the moniker 'false step', implying its lack of utility. Thus, a significant debate has developed among coaches regarding the value of this phenomenon. This study examined the false step through a comparison with a forward step condition, where participants were only allowed to step forward to initiate a sprint. Comparisons were made between velocity products as well as mechanical antecedents during the first milliseconds of sprint initiation. Participants were 30 healthy college-aged student-athletes, who were asked to perform three false step and forward step sprint trials. Timing gates and 3D modelling were used to examine velocities and mechanical variables during these trials. Overall, results demonstrated that the false step was significantly (p < 0.001) faster (0.23s; 9.44%) over a ten-metre sprint. Additionally, angular variables of the ankles during sprint initiation were found to be significantly different between false and forward step conditions. Findings suggest that the false step may be beneficial for athletes and is an advantageous technique for achieving a rapid change in velocity.